2022
DOI: 10.11591/ijece.v12i5.pp5553-5561
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction prediction of online education in COVID-19 situation using data mining techniques: Bangladesh perspective

Abstract: <span>This research focuses on the education-based online learning platform. Due to the <a name="_Hlk109304176"></a>coronavirus disease (COVID-19) epidemic, online education is gaining global popularity. It has shown how successful it is in investigating the quality of online education at the COVID-19 pandemic situation by 799 students from different academic institutions, schools, colleges, and universities. A Google web form has been utilized as the data gathering mechanism for this survey.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Image data, in contrast to temporal information, has a topology that is just two-dimensional. This model may be used to time series prediction with great performance, as demonstrated by this state-of-the-art research [28]. Cell state ct and filtered input ot control the output layer, which selects the result.…”
Section: Related Workmentioning
confidence: 99%
“…Image data, in contrast to temporal information, has a topology that is just two-dimensional. This model may be used to time series prediction with great performance, as demonstrated by this state-of-the-art research [28]. Cell state ct and filtered input ot control the output layer, which selects the result.…”
Section: Related Workmentioning
confidence: 99%
“…The Decision Tree model has the lowest accuracy, according to a comparative study, at 82.29%. In Poushy et al [17] analysis, they obtained 93.75% (LR and SVM) accuracy in their dataset, which indicated that the majority of students are dissatisfied with the way that online classes are currently being run and the speed of the internet.…”
Section: Customer Satisfaction Predictionmentioning
confidence: 99%
“…Based on the test results, the Naïve Bayes Method can be used to predict how satisfied a lecturer will be with the performance of the institution. In Poushy et al [17] analysis, they obtained 93.75% (LR and SVM) accuracy in their dataset, which indicated that the majority of students are dissatisfied with the way that online classes are currently being run and the speed of the internet. In contrast, when compared to LR, KNN, and SVM, Naïve Bayes is the classifier with the lowest accuracy.…”
Section: Customer Satisfaction Predictionmentioning
confidence: 99%
“…Institute of Technology PLN is a private university which during the pandemic used the Microsoft Teams as an online learning medium, and now Microsoft Teams is still used to support hybrid learning (online and offline). The research also to find out how student acceptance during online learning is towards the use of technology, especially Microsoft Teams [33].…”
Section: Introductionmentioning
confidence: 99%